THE EFFECT OF THE ORIENTATION OF A CRACK ON THE CRITICAL BUCKLING LOAD IN A HYBRID COMPOSITE. (Sciences & Technologie. B, Sciences de l'ingénieur, 2016)
In this work an analysis of buckling was carried out on rectangular plates hybrid composites with and without circular notch using the finite element method. The buckling strength of the laminated plate subjected to the uniaxial compression is highlighted according to the orientations of the fibers. The results show that increasing the thickness of the aluminum layer significantly improves the resistance to buckling. Whatever the orientation of the crack the critical buckling load remains stable.